Perilaku Konsumtif Mahasiswa Pengguna Shopee Paylater - Mursalina, Adinda; Hasanah, Hasanah; Efriani, Efriani (Balale' : Jurnal Antropologi, 2024)
This research has examined consumer behavior and the use of Shopee PayLater in online shopping for students in Sepakat 2 Southeast Pontianak. Shopee Paylater is known as a service for users to shop online on the Shopee platform without having to pay directly. The type of research that has been used is a descriptive qualitative research method. This research has focused on consumer behavior, factors, and the impact of using PayLater services in online shopping by students in Sepakat 2 Southeast Pontianak analyzed using Jean Baudrillard's consumption society theory. The results of the research have shown that there are two factors in the consumptive behavior of students using Shopee Paylater, namely: internal factors caused by emotional feelings, habits, social status, lack of financial awareness, impulsivity, and lifestyle while in terms of external factors caused by promotions and discounts, convenience access, attractive advertising, flexible payment features, reviews and testimonials, personalization technology, loyalty and rewards programs and exclusive offers. Thus, consumer behavior using Shopee Paylater can become a problem if users do not pay attention to their spending limits and financial capabilities. It is important to use Shopee Paylater wisely by considering financial needs and capabilities.